Daya Adaptasi Lalat Buah (Bactrocera calumniata H.) pada Tanaman Inang Cucurbitaceae pada Dataran Tinggi di Bali - I GEDE DYLAN GUNASTRA; I WAYAN SUSILA; NI NENGAH DARMIATI (Fakultas Pertanian Universitas Udayana, 2023)
Adaptability of Fruit Flies (Bactrocera calumniata H.) to Cucurbitaceae Host Plants in the Highlands of Bali. Plants from the Cucurbitaceae family are one of the host plants for fruit flies. Plants grow in the highlands and lowlands. One of the pests of the Cucurbitaceae family is Bactrocera calumniata. Symptoms of fruit attacked by B. calumniata are having small holes that ooze fluid caused by the puncture of the ovipositor of female fruit flies and fruit that is attacked after a long time becomes soft in texture and smells rotten. The research was conducted in Candikuning Village, Tabanan Regency and Pancasari Village, Buleleng Regency, Bali Province. Based on research showed that zucchini and cucumber were attacked by fruit flies of the type B. calumniata. Abundance of population, percentage of females, and percentage of damage were more on zucchini plants than cucumber plants. So the adaptability of the fruit fly B. calumniata is better in the zucchini plant compared to the cucumber plant.